Reflection and Reconstruction of Patients' Informed Consent Protection System in Doctor-patient Relationship - Qiheng LIU; Xiaoli TAN (Yixue yu zhexue, 2025)
The inadequate protection of patients' informed consent rights is an important reason for the disharmony in doctor-patient relationship. Currently, Chinese law primarily focuses on protecting patients' passive right to be informed about medical treatments, while lacking sufficient protection for their active right to seek medical information. The existing legal framework for protecting informed consent is flawed and should be reconstructed by establishing a dual-protection mechanism. This mechanism should be based on the medical institution's fulfillment of its statutory duty to inform while also ensuring patients' proactive access to information. By strengthening the protection of the active right in the informed consent right of patients, the mechanism will not only enhance their understanding of treatment information but also assists medical staff in fulfilling their duty to inform. This approach fosters mutual understanding and trust between doctors and patients, offering a new theoretical path for the building of a harmonious doctor-patient relationship.